Nanofabricação, caracterização e modelagem de dispositivos optoeletrônicos nanoestruturados de corantes orgânicos - COSTA, Sheila Cristina dos Santos (Universidade Federal do Pará, 2017)
To better understand the process of miniaturization and the behavior of molecular structures under this effect we appeal to the calculations based in Quantum Mechanics (QM) with the purpose to corroborate theoretical and experimental data as electronic structure as well as electric properties. Another method sufficiently known consists simulate solute-solvent effect through the probabilistic Monte Carlo (MC) method. Of ownership of these computational tools we develop simulations QM/MC that translate the behavior of organic composites Methyl Red (MR) and 1,4-bis (5-phenyl-2-oxazolyl) benzene (POPOP), when suffer structural changes, modification in the optic answers, etc., due miniaturization processes, environment variations, external actions. The Methyl Red composite is known as a sensible dye of pH variation and meets in the basic and acid (isoeletrônico, zwitteriônico) forms is classified as azo-composite for the presence of (– N = N –) bonding in its structure. The POPOP is a luminescent dye of intense fluorescence in the blue region of the UV-Visible spectrum; we stand out that to investigate the functional and mannering principles of this structure we consider two conformational structures protonated derivatives of POPOP: C1 (N+) and C2 (N+). Initially all organic composites structures of MR and POPOP had been optimized through of the quantum methods: semiempirical PM3 (Parametric Method 3) and ab initio HF (Hartree-Fock) and DFT (Density Functional Theory), getting the geometric parameters and the conformations of lowest energy of each system, for the study of the electronic structure. Sequentially, two distinct stages of simulation had been used for the study of composites: 1st) The MR and POPOP structures had been optimized through the method PM3 + External Electric Field (the EEC), getting the geometric parameters and charge parameters. We use this method with the purpose to simulate the electronic transport properties of organic composites as the electric reply characterized by the charge transport (e) curve in function of the variation of the tension (V) in the structures. By means of the electric reply [(e) × V] we characterize this function to use them in nanostructured devices, as photodiodes, photodetector, solar cells, etc. The 2nd stage consists of simulate organic composites through the Monte Carlo method, to investigate its behaviors in liquid. The systems distinct consist of the addition of VM (basic, acid: isoelectronic and zwitterionic) and POPOP [C1 (N+) and C2 (N+)] in 1000 water molecules to analyze the solute-solvent interactions for development of interchange systems optoelectronic systems as sensory. In MC simulation had been carried 1×1010 steps MC for both thermalization and equilibrium stages in NVT ensemble. Generate a set of 105 configurations, from these we select a set reduced of 103 descorrelantion configurations of which we obtain the convergence average of the electronic transitions π→π*. The convergence average of the electronic transitions π→π* for MR: basic s of 434.33 ± 1,0 [436,34 ± 2,0 nm], isoelectronic 485,80 nm ± 2,0 nm [480,66 nm ± 3,0 nm], and zwitterionic [502.13 nm ± 3.0 nm]; for POPOP C1 [361,25 nm ± 2,0 nm], C1(NP+P) [485.0 ± 26.0 nm], C2 [355,39 nm ± 3,0 nm] and C2(NP+P) [472.0 ± 24.0 nm]. The averages of the electronic transitions π→π* had been obtained through semiempirical ZINDO/S-CIS (Zerner Intermediate Neglect of Orbital Diffential Spectroscopic - Configurations Interaction, Single excitation) method that better translates the spectroscopic parameters of the organic molecules in the UV-visible region. Experimentally we develop two distinct types of systems through of the techniques: Sol-Gel that consists in the incorporation of composites in host matrix of APP (Aluminum Polyphosphate), and Blendes that consist in the manufacture of volume devices within active monolayer. The MR and POPOP composites had been diluted in hybrid solution (10% etanol + 90% water), aliquots of these solutions had been incorporated in the synthesis of APP/Gel. The samples obtain for the Sol-Gel process had been submitted to the variation pH and characterized by spectroscopy of absorption in the UV-Visible region, whose bands of maximum absorption are of [431 nm, 513 nm, 511 nm] for MR and [358 nm, 511 nm and 472 nm] for POPOP and values of [355 nm, 361 nm] for POPOP in solution, that corroborate the theoretical results from the averages of the electronic transitions π→π*. The monolayer devices of MR and POPOP had been manufactured by overlapped of thin films in vitreous substrate/FTO (1st electrode)/PEDOT/P3HT/ active monolayer -Aluminum (2nd electrode) and characterized electrically for charge density (J) in function of applied voltage (V), under dark current and under 550 nm monochromatic light. The MR devices present curve (J×V) characteristic of a rectifier junction p-n of higher electric current signal under reverse polarization for dark current, being this signal intensified under light 550 nm; under forward bias the device presents the same behavior how much to the current signal, this is intensified when measured on monochromatic light (550 nm) in comparison with dark current, however under reverse polarization and forward bias the device presents curve characteristic (J×V) analogous of the conventional photodetector and diode tunnel. For POPOP intensification of the electric chain signal is observed under forward bias and reverses when the devices are under monochromatic light in comparison with measures made under dark current, in way that the characteristic curve (J×V) has similar behavior of the conventional photodiodes. The theoretical-experimental results of the electric (J×V) properties of composites had presented similar behaviors in the voltage range [- 2.0 V – 2.97 V] for MR and [- 2.86 V - 2.86V] for POPOP. We development a complete study with polymers of low bandgap (gap 1 eV) based in monomers bridges composition for carbon forming polymeric chains had been investigated by the methods AM1 (Austin Model 1), PM3 and DFT [B3LYP/6-31G] to corroborated the results of the oligomers of CDM (4-dicyano methyllene-4H-cyclopente [2.1 - 3: 4-b'] dithiophene) and BDT (1,3-benzodithiole-4H-cyclopenta [2,1-b: 3,4-b'] dithiophene), derived from the ditiophene. The results show that the growth of the polymeric chain formed by monomers of CDM and BDT provokes the reduction bandgap of the oligomers, analogous behavior to the polymers based on (3-alkylthiophenes) whose electronic transition π→π* energy is of 1.67 eV, the maximum absorption of the CDM and BDT are of 1.28 eV and 1,73 eV, respectively The theoretical methods used in this study to describe satisfactorily this behavior, whose maximum absorption is of approximately 1,28 eV for CDM and 1,74 eV for BDT, these results had been obtain from the polymeric chains formed by 5 monomers units, demonstrating that the geometric conformations of the polymeric chains simulated are equiprobability, proving the trustworthiness of the methods used in our investigation. In general lines, the results presents to demonstrate that the organic composites investigated are good candidates for employ in nanostructured organic devices applied in the molecular electronics and new technology of materials.